Sharia Capital Market Contribution to the Development of National Capital Market Legal - Rodhibillah, Fasha (Institut Agama Islam Negeri Lhokseumawe, 2024)
The problems in this research are: what is the position of the sharia capital market with national capital market law and what are the implications of the sharia capital market and its contribution to the development of national capital market law. The objectives of this research are: understanding the position of the sharia capital market with national capital market law and understanding the implications of the sharia capital market and its contribution to the development of national capital market law. This research uses normative juridical methods by examining library materials including research on legal principles, comparative law, and legal history. The specifications of this research are analytical descriptive. The data sources used in this research are primary legal materials and secondary legal materials. Meanwhile, the analysis used in this research is qualitative analysis. The results and conclusions of the research show that the position of the sharia capital market and national capital market law are closely related to national economic development. It can be seen that the principles of the Sharia capital market cover all the principles of an ideal capital market. However, there are several things that emphasize halal products/services from business activities, specific business activities with clear benefits, fair profit sharing mechanisms both in terms of profits and losses according to the participation of each party and fair market mechanisms and the principle of prudence. Be careful with both issuers and investors.